A Dimeric η1, η5‐Germole Dianion Bridged Titanium(III) Complex with a Multicenter Ti−Ge−Ge−Ti Bond. Issue 28 (12th June 2018) - Dong, Zhaowen; Janka, Oliver; Kösters, Jutta; Schmidtmann, Marc; Müller, Thomas
Abstract: Dimeric germole dianion bridged Ti III and Zr IV complexes have been synthesized. In these complexes, the germole dianion adopts a formal η 1, η 5 coordination to the two metal centers. The bonding situation in these bridged dimers is dominated by a covalent Ge−Ge interaction that results, for example, in a strong antiferromagnetic coupling of the d 1 Ti centers. Abstract : The multifarious coordination pattern of aromatic germole dianions is demonstrated by the synthesis of dimeric Ti III and Zr IV complexes. Computational analysis revealed an unexpected covalent Ge−Ge interaction that influences the properties of these complexes.